Introduction and Demo of Virtual Reality Technology to Initiate Active Learning in Architectural Design - Ridzqo, Intan Findanavy; Demami, Aliviana (Journal of Artificial Intelligence in Architecture, 2024)
Architectural education is adapting to the demands of efficient, technology-driven practices, with virtual reality (VR) emerging as a critical tool in bridging communication gaps between architects and clients. This study, conducted by lecturers at Institut Teknologi Indonesia, focuses on their experience implementing VR technology in the High-rise Building Technology class. The initiative spans four sequential stages, with the introduction and demo executed hybridly (online and offline). The authors emphasize the importance of knowledge induction and firsthand demonstrations to familiarize students with VR. Notably, external instructors proficient in VR technology participate in the program. Student engagement and enthusiasm are evident, with offline demo attendance surpassing the online VR introduction seminar. The COVID-19 pandemic has affected students' motivation to learn, and the hands-on VR experience is a revitalizing approach. The two-way interaction between instructors and students enhances interest in in-person attendance. The authors advocate for the continued development of this experience in architectural education, promoting an active learning system using VR across various courses. The paper underscores the potential of VR technology to invigorate architectural education and enhance student engagement in the post-pandemic learning landscape.